Constraining subduction-collision processes of the Paleo-Tethys along the Changning-Menglian Suture: New zircon U-Pb ages and Sr-Nd-Pb-Hf-O isotopes of the Lincang Batholith - Deng, J.; Wang, C.; Zi, Jianwei; Xia, R.; Li, Q. (Elsevier BV, 2017)
The Changning-Menglian suture represents a remnant of the main Paleo-Tethys in the Sanjiang Orogen (SW China), and preserves abundant magmatic rocks formed during orogenic processes related to the closure of the Paleo-Tethys. Our geochronology study on granitoids of the Lincang Batholith, a prominent magmatic feature along the Changning-Menglian suture, yields crystallization age of 261±1Ma, 252±1Ma, to 203±1Ma, confirming a multi-stage emplacement of the batholith. The Late Permian granodiorites are medium- to high-K calc-alkaline, metaluminous (A/CNK=0.99-1.10), with high Al 2 O 3 content (14.03wt%), high Mg # (46), high ( 87 Sr/ 86 Sr) i (0.7192-0.7278), negative whole-rock e Nd (t) (-14.7 to -8.5), ( 206 Pb/ 204 Pb) t of 18.199 to 18.791, ( 207 Pb/ 204 Pb) t of 15.714 to 15.765, ( 208 Pb/ 204 Pb) t of 38.500 to 38.851, zircon d 18 O SMOW =7.13‰-8.57‰, and zircon e Hf (t) of -14.8 to +0.4. The Late Triassic granites are characterized by high SiO 2 value (68.52wt%), high Mg # values of 50, with negative Eu anomalies (dEu=0.32-0.78), high ( 87 Sr/ 86 Sr) i (0.7202-0.7424), negative whole-rock e Nd (t) (-15.6 to -10.7), ( 206 Pb/ 204 Pb) t of 18.659 to 18.793, ( 207 Pb/ 204 Pb) t of 15.752 to 15.791, ( 208 Pb/ 204 Pb) t of 38.865 to 38.959, zircon d 18 O SMOW =8.07‰-9.76‰. These geochemical and isotopic features suggest that the primary magma of both Late Permian and Late Triassic granitoids most likely originated from partial melting of the underlying Proterozoic crustal rocks, with limited addition of mantle components. Our new geochronological and geochemical results together with previously published data, suggest that the composite Lincang Batholith records three magmatic episodes related to the Paleo-Tethys evolution, corresponding to subduction (prior to ~252Ma), syn-collisional (250-237Ma), and post-collisional (235-203Ma) stages.